Hubungan Intensitas Penggunaan Media Sosial dengan Gejala Depresi pada Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen - Sitepu, Jenny Novina; Siringoringo, Priparty Intan Sukma; Girsang, Rosminta (Universitas HKBP Nommensen, 2022)
ABSTRACT Background: Social media is an inseparable component of human life, included medical students. Social media usage has both positive and negative benefits. Several studies showed excessive use of social media can cause mental health problems, such us depression. This study aims to evaluated the correlation between the intensity of social media use and the degree of depressive symptoms in students of the Faculty of Medicine, University of HKBP Nommensen. Methods: Analytical observational study with cross-sectional design was conducted on 101 students of the Faculty of Medicine, University of HKBP Nommensen using questionnaires such us Social Networking Time Use Scale (SONTUS) to measure the intensity of social media use, and Beck Depression Inventory-II (BDI-II) to assess the degree of depressive symptoms. Data analysis were done by using the Spearman's rank correlation coefficient test. Results: This study showed that 38.6% respondents had low intensity, 41.6% medium intensity, and 19.8% respondents had high intensity of social media usage. There were 81.2% of respondent had no depression, 10.9% had mild depression, 5.9% moderate depression, and 2.0% severe depression. The Spearman test results showed that there is no correlation between the intensity of social media usage and the degree of depressive symptoms (p = 0.882) with a very weak correlation value (r = 0.015). Conclusion: There is no correlation between the intensity of social media use and the degree of depressive symptoms in the Faculty of Medicine, University of HKBP Nommensen students. Keywords: Social media, depression, medical students.